A Life Cycle Risk Management Framework for Green Building Project Stakeholders - Koc, Kerim; Kunkcu, Handan; Gurgun, Asli Pelin (ASCE-AMER SOC CIVIL ENGINEERS, 2023)
The construction industry compromises the sustainability of the built environment because of its adverse impacts on the environment, economy, and society. In response, green building (GB) projects advocate for targeted sustainability goals while some particular risks in GB projects could cause several unfavorable outcomes. This study aims to assess the life cycle risks of GB projects and emphasize the role of stakeholders in the management of corresponding risks in a four-step analysis procedure. In the first two steps, a comprehensive literature review and focus-group discussion were employed to construct the decision-making framework suitable to the GB life cycle. A fuzzy analytical hierarchy process (AHP) was used to prioritize the identified risks based on expert opinions. The fuzzy technique for order preference by similarity to ideal solution (TOPSIS) was used to associate stakeholders' role with the management of GB risks that might arise throughout GB projects. Findings indicate that lack of experienced green construction staff, limited availability and reliability of green subcontractors and suppliers for the specific requirements of GB, and inflation of green materials' prices are ranked as the most significant risks. A generic life cycle risk management framework for green buildings was developed to analyze the most significant risks and corresponding stakeholders. By addressing the gap in the literature, this study is expected to engage practitioners and GB project stakeholders for more effective and robust risk management frameworks.
Keywords: Green building (GB) life cycle; Sustainable construction; Multicriteria decision-making (MCDM); Risk management; Green building (GB) stakeholders; FUZZY SYNTHETIC EVALUATION; DECISION-MAKING APPROACH; DEVELOPING-COUNTRIES; TECHNOLOGIES ADOPTION; PRIORITIZING RISKS; TOPSIS; AHP; SELECTION; BARRIERS; Engineering